2008
DOI: 10.1210/jc.2008-0311
|View full text |Cite
|
Sign up to set email alerts
|

High Risk of Hypopituitarism in Patients Who Recovered from Hemorrhagic Fever with Renal Syndrome

Abstract: A high prevalence of hypopituitarism after recovery from HFRS is identified, with magnetic resonance imaging revealing atrophic pituitary and empty sella. Awareness is raised to neuroendocrine consequences of HFRS because unrecognized hypopituitarism significantly affects the physical and psychological well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 30 publications
2
37
0
1
Order By: Relevance
“…In a recent retrospective Serbian study the prevalence of any endocrine deficiency 2 years after HFRS was 18 % [14].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a recent retrospective Serbian study the prevalence of any endocrine deficiency 2 years after HFRS was 18 % [14].…”
Section: Discussionmentioning
confidence: 98%
“…PUUV antigen has been detected in hypophyseal neuroendocrine and endothelial cells of a patient with fatal NE [8]. In a recent retrospective Serbian study of 60 adults with a previous HFRS, a high prevalence of hypopituitarism was identified after recovery from HFRS [14]. Immunological factors including tumor necrosis factor alpha (TNF-α) and interleukin-6 (IL-6) have been suggested to be involved in the pathogenesis of NE [15].…”
mentioning
confidence: 99%
“…Hypopituitarism associated with hemorrhagic fever with renal syndrome has not been reported elsewhere (4)(5)(6)(7)(8). The exact mechanism of the hypopituitarism is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Pekic et al (8) described the first report of hypopituitarism that developed as a sequel of HFRS in the region of the Balkans and then sporadic cases have been presented. They reported three cases 24 They found a high prevalence of hypopituitarism (18.3%) in patients who recovered from HFRS many years ago.…”
Section: Discussionmentioning
confidence: 99%
“…A large study investigated patients two years after CNS infections, and isolated corticotroph deficiency was diagnosed in some patients (66 (78,79). In a large retrospective study (60 adults who recovered from HFRS), high prevalence of partial or complete hypopituitarism was found in HFRS survivors (80). In a recent study, a group of patients suffering from Puumala hantavirus infections were followed long term.…”
Section: Viral Hypophysitismentioning
confidence: 99%